Symptom attribution and treatment seeking in Australian veterans. (September 2020) - Wright, Breanna K; Kelsall, Helen L; Clarke, David M; McFarlane, Alexander C; Sim, Malcolm R
To understand the role of symptom attribution in treatment-seeking behaviours, survey results of 1356 veterans (age = 38–72 years) were analysed. Controlling for symptom frequency, significant relationships were found for specialist and psychological-related consultations. Those who favoured psychological explanations for symptoms were more likely to attend specialist and psychology-related consultations and filled significantly more prescriptions than people who predominantly explained symptoms by situational factors (normalisers). Veterans who favoured somatic explanations attended more general practitioner consultations than normalisers. Attributional style should be considered part of the constellation of factors influencing healthcare usage. Normalisers, the predominant group, used fewest health services and filled fewest prescriptions; this may have important implications for healthcare considering their tendency to minimise or downplay symptoms.